Correlates of partial tooth loss and edentulism in the Brazilian elderly - Hugo FN, Hilgert JB, de Sousa MLR, da Silva DD, Pucca Jr GA. (Blackwell Synergy, 2007)
In South American older adults the association between tooth loss and demographic, predisposing and enabling factors has not been determined.